Can green banking help promote and enforce sustainable development? The case study of Egypt - Atef, Nuran Ashraf (AUC Knowledge Fountain, 2017)
The world is now witnessing massive climate change impacts and threats that are rendering numerous areas vulnerable to adverse consequences. The rapid global population growth is straining the demands on the natural resources as a result to the increased consumption and production patterns in the economic field all over the world. As such, the global economy ought to explore alternative approaches to its operations that consider the social and environmental aspect of their impacts. This new approach calls for the support of the private sector to govern the sustainable development integration as part of the economic growth model. Hence, capitalizing on the banking sector’s key influential role in the economy to provide access to finance for projects is an asset. This research explores the viability of applying this concept in Egypt as a climate change vulnerable developing country struggling out of an economic recession. The literature review indicated a shortage in literature on developing countries and particularly Egypt in terms of green banking and promoting sustainability through the financial sector. The research begins by identifying the key concepts of Sustainable Development, and Green Banking on a global scale, Green Banking in Egypt and the main instruments used to apply sustainability within banking operations. This foundation provides a base for he focus of this research: integrating sustainability in the lending operations of banks for corporate customers by indicating the academic findings and highlighting gaps in the literature. As such, this research aims to bridge the gap in studies between sustainable development and access to finance in developing countries, and present an attempt for policy recommendation to promote and enforce sustainable development. The research was conducted in a qualitative, descriptive approach using different methods as observation, online review of publications, and in-depth interviews. Global case studies were explored as good case practices to support the findings obtained from the conducted interviews with banks in Egypt. This allowed comparison and contrasting established approaches in other countries with similar realities, and compensated the shortage of literature on Egypt. The result on the viability of applying sustainability was dependent on the benefits to the banking sector resulting from the adoption. As such, the research addressed the benefits to the banks in order to base a strong case to mainstream the concept across the sector using Performance (net profits and market share), and Risk Management (risk procedures and efficiency). It was evident in the analysis chapter that there were no direct benefits in terms of Performance, contrary to Risk Management, and other non-financial benefits that indirectly contribute to profitability were found as well. Hence, a policy recommendation was developed in the concluding chapter as an attempt to provide a recommended path to mainstream, promote, and enforce sustainability based on global good case practices and conducted interview findings.